Energy partition and nitrogen utilization by male goats fed encapsulated calcium nitrate as a replacement for soybean meal - Silveira, R. F. [UNESP]; Fernandes, M. H.M.R. [UNESP]; Almeida, A. K. [UNESP]; Araujo, R. C.; Biagioli, B. [UNESP]; Lima, A. R.C. [UNESP]; Teixeira, I. A.M.A. [UNESP]; Resende, K. T. [UNESP] (Elsevier, 2019)
Encapsulated calcium nitrate (ECN) has been studied as a source of non-protein nitrogen (NPN) that establishes an alternative sink of free hydrogen in the ruminal environment and, consequently, reduces the emission of methane and probably improves efficiency of energy use. The aim of this study was to assess the impact of ECN as a substitute for soybean meal (SBM) in energy partition, substrate oxidation, and microbial nitrogen (MicN) synthesis. Twelve growing castrated male goats (21.9 kg ± 3.19 kg of initial body weight) were used in four 3 × 3 Latin squares (LS) during three 48-d periods. Goats were grouped by body weight (BW) within each LS and randomly assigned to one of three diets: SBM – control based on SBM, 75 g/kg of SBM on dry matter (DM) basis; ECN12.5 – 12.5 g/kg of ECN on DM basis; and ECN25 – 25 g/kg of ECN on DM basis. Each period included 21 days for adaptation, five days for metabolism trials (d 22 to d 26), and 15 days for indirect calorimetry trials (d 27 to d 41). At the end of each period, a 7-day washout interval was provided during which the goats were fed SBM diet. The goats showed no symptoms of intoxication based on methemoglobin (MetHb) levels (0.7% ± 0.17 of total hemoglobin). Heat production (HP) was not influenced by treatments (P = 0.91), but fast heat production (FHP) was 22% (P < 0.05) lower in ECN25 than in SBM. Methane emission decreased by 0.21 g for each g of nitrate intake. The inclusion of 9.5 g/kg of ECN on DM resulted in a maximum DE and ME intake. The total retained N decreased linearly (P < 0.05) with the increase of ECN; however, microbial nitrogen (MicN) synthesis did not differ between treatments. In conclusion, the use of ECN as a replacement for SBM decreased FHP, which might spare energy for growth. The use of ECN as a substitute for SBM did not affect MicN synthesis. The inclusion of 9.5 g/kg of ECN on DM basis results in maximum DMI, DE, and ME intake in growing goats.
Keywords: Digestibility; Greenhouse gas; Indirect calorimetry; Nitrogen balance; Respirometry